International initiatives and works of the First President of the Republic of Kazakhstan N. Nazarbayev in the field of global security - Kakenova Г.М.; Sahova Б.С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2020)
The article analyzes the international initiatives of the First President of the Republic of Kazakhstan-Leader of the Nation N. A. Nazarbayev in the field of global security in the context of his presidential powers, works and research related to state problems. Issues of international security and non-proliferation of nuclear weapons are now one of the priority areas of development in the political life of any state. It is proved that any changes in this sphere have greatly affected the international situation of many countries of the world and Kazakhstan.